Review of resilience hubs and associated transportation needs. (December 2022) - Ciriaco, Thayanne G.M.; Wong, Stephen D.
Highlights: We reviewed concepts and examples of resilience hubs in North America. Resilience hubs can build social cohesion and preparedness for multiple hazards. Resilience hubs can operate during disasters and everyday conditions. Transportation is currently not integrated in hub placement, design, or planning. No metrics or empirical evidence currently guide the implementation of hubs. Abstract: Rapid urban growth and the devastating impacts of disasters and emergencies have challenged infrastructure and social systems in many communities. Recently, the nascent concept of "resilience hubs" has emerged to help communities overcome these challenges and improve well-being during disasters and everyday conditions. This paper provides an early conceptual understanding of resilience hubs, in particular their associated transportation needs, through a comprehensive literature review. The review identified characteristics and needs for planning hubs by focusing on their current definitions and related concepts (e.g., evacuation shelters, mobility hubs). In all, the review identified that resilience hubs could be a successful tool for communities in addressing the important needs of residents, evacuees, and survivors. However, we found that the placement of hubs is not methodical or optimized, and hubs have yet to be evaluated using metrics or key performance indicators. Critically, most literature and examples of resilience hubs fail to consider: 1) how people and relief supplies will travel to/from hubs, or 2) potential transportation services that could be offered by hubs. We recommend that programs that identify, design, and create resilience hubs should emphasize mechanisms for providing reliable and equitable transportation for people and relief supplies.